The Difference of Students’ Learning Outcomes between STAD Model and Discussion Model on Economics Subject - Ruski, Ruski (Fakultas Ekonomi, Universitas Negeri Semarang, 2016)
This research aims to identify the difference of students’ learning outcomes between STAD cooperative learning model and discussion model on economics subjects. This research was conducted at class X Senior High School 1 in Surabaya. It was an experimental study using a Nonequivalent Control Group Design research design. The total numbers of students were 140 students. Samples were taken by using purposive random sampling technique. 69 students were analyzed as sample. They were divided into two classes. One class was as a control class (X IPS3) with 35 students and another was as experimental class (X IPS1) with 34 students. Collecting data used post test and pre test. Findings show that there are differences on students’ learning outcomes significantly between STAD cooperative learning model (experimental class) and discussion (control class) on economics subjects. It is proven by the results of the calculation of the Z test was greater than 0.05 (4.679 > 0.05), hypothesis is accepted and the mean score at experimental class is higher than the control class (82.29 > 74.03). Thus; the implementation of STAD method gives good influence on students’ learning outcomes.